2019
DOI: 10.1371/journal.pone.0215002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of assistive products to promote functional independence in self-care activities in the bathroom

Abstract: In homes, problems in daily functioning of older people often occur in the bathroom, especially in the transfers to the toilet and/or shower/bath. Assistive products have the potential to maximise functional independence (i.e. performance without assistance from another person) in everyday activities; however, more research is needed to better understand the impact of this technology on independence in the transfers in the bathroom. Additionally, little is known about the role of the environmental factors in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Studies in the literature suggest that the effect of assistive devices on depression levels may be different across age (Zimmer & Chappell, 1994), gender (Frochen & Mehdizadeh, 2018), health status (Eek & Wressle, 2011), residential environment and social preferences (De‐Rosende‐Celeiro et al, 2019). Accordingly, controlling for the same variables as in the baseline regression analysis, including health status, 7 this study examined the heterogeneity of the effects of assistive devices use on depression levels in older adults in four dimensions: gender, age, urban/rural and socialisation 8 (see Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the literature suggest that the effect of assistive devices on depression levels may be different across age (Zimmer & Chappell, 1994), gender (Frochen & Mehdizadeh, 2018), health status (Eek & Wressle, 2011), residential environment and social preferences (De‐Rosende‐Celeiro et al, 2019). Accordingly, controlling for the same variables as in the baseline regression analysis, including health status, 7 this study examined the heterogeneity of the effects of assistive devices use on depression levels in older adults in four dimensions: gender, age, urban/rural and socialisation 8 (see Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…National and international researchers have identified that in home care for dependent elders, bathing is generally the activity of daily living that most causes problems in elders' and their caregivers'/ family members' lives (3)(4) . In Western culture, personal hygiene is one of the most sensitive and intimate subjects and is commonly carried out in privacy.…”
Section: Introductionmentioning
confidence: 99%
“…Although physical impairment is often considered as the base of disability, it has long been acknowledged that ADL disability is caused by both a mixture of body limitations and environmental barriers (Verbrugge & Jette, 1994;World Health Organization, 2015). Environmental factors could play an important role in influencing the outcome of ADL tasks (De-Rosende-Celeiro et al, 2019;Iwarsson, 2005;Lim et al, 2020). In the World Report on Disability, special emphasis is placed on how environmental factors such as the built environment, social support, and policies can facilitate access or create barriers that affect participation, strengthening the need for existing disability studies to examine both the human body as well as its interactions with the environment (World Health Organization, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies specifically exploring the relationship between bathing disability and environmental factors are scarce, and most of the literature on bathing disability has been focused on the interventions inside the modern bathroom through the use of assistive technologies such as grab rails and bath transfer benches (Aminzadeh et al, 2001;De-Rosende-Celeiro et al, 2019;Gill et al, 2007;Naik & Gill, 2005). It is worth noting that a recent study by Liu et al (2020) reported that Chinese rural older adults may have up to four bathing methods (such as showering indoors, bathing indoors, use of public bathing facilities, or bathing outdoors), unlike their urban counterparts for whom bathroom facilities are usually modernized and standardized.…”
Section: Introductionmentioning
confidence: 99%